Perceptions about Energy Drinks are Associated with Energy Drink Intake among U.S. Youth. Issue 4 (March 2015) - Kumar, Gayathri; Park, Sohyun; Onufrak, Stephen
Purpose: Energy drinks are growing in popularity among youth because of their stimulant properties. However, they can increase blood pressure and are associated with serious consequences such as cardiac arrest. This study examined the associations between energy drink perceptions and energy drink consumption among youth. Design: The design was a cross-sectional study using the YouthStyles Survey 2011. Setting: The online survey was administered at home. Subjects: Subjects were youths aged 12 to 17 years in the summer of 2011 (n = 779). Measures: Energy drink consumption, perceptions about energy drinks, and sociodemographic and behavioral variables were measured. Analysis: Chi-square and multivariable logistic regression analyses were used. Results: Overall, 9% of youth drank energy drinks, 19.5% agreed that energy drinks are safe drinks for teens, and 12.5% agreed that energy drinks are a type of sports drink. The proportion of youth consuming energy drinks once per week or more was highest among youth aged 16 to 17 years and among those who are physically active three to six times a week. The odds for drinking energy drinks once per week or more was higher among youth who agreed that energy drinks are safe drinks for teens (odds ratios [OR] = 7.7, 95% confidence intervals [CI] = 3.6, 16.4) and among those who agreed that energy drinks are a type of sports drink (OR = 5.0, 95% CI = 2.4, 10.7). Conclusions: These findings suggest that many youth may be unaware or misinformed about the potential health effects and nutritional content of energy drinks. Efforts to improve education among youth about the potential adverse effects of consuming energy drinks are needed.